Frequency of hidden Hepatitis B and C during screening in patients’ undergone surgical procedures: Single Centered study: Hepatitis B and C During in Patients’ Undergone Surgical Procedures - Hussain, Arsalan; Hussain, Afzal; Afzal, M Faheem; Hussain, Rutaba; Hameed, Maryam (Pakistan Journal of Health Sciences, 2022)
Hepatitis is the serious health related concern and spreading rapidly specifically in developing countries, it also led to liver related diseases and hepatocellular carcinoma. While liver disease is an important health problem and having high health cost and leads to poor quality of life and dependency. Objectives: To determine the Incidence of hidden Hepatitis B and C during screening in patients’ undergone surgical procedures reported in a single center. Methods: A cross-sectional study was conducted in Innovative Health Concepts & Research center by using a non-probability convenient sampling technique. The duration of study was 8 months from December 2021 to August 2022 and the study included those subjects who admitted in hospital for some surgical procedure and both genders aged between 25 to 60 years. Those subjects who have multiple neurological or musculoskeletal or endocrinological condition and came for the 2nd procedure were excluded from the study. Ethical permission was sought from Board of Advance Studies and Expert Review Board of Innovative Health Concepts Hospital (ASRRB/IHC&RC/RH/MED/Letter-003). The assessment for hepatitis B, HCV, and HIV was done through blood test. Data was entered and analyzed through SPSS version 26. Results: The results of study showed mean age of subjects was 43.47±10.17, mean weight was 71.35±10.78. The result showed 04% prevalence of hepatitis B, 4.9% prevalence of hepatitis C and no case reported of Human Immunodeficiency Virus (HIV). Conclusion: The study concluded that there is very low frequency of hepatitis B and C found in subjects undergone surgical procedures